Women’s Gender Equality in the Perspective of Gaudium Et Spes Art. 9 and 29 - Fransesco Agnes Ranubaya; Yohanes Endi (Universitas Muhammadiyah Malang, 2023)
The Catholic Church always provides space to fight for justice and gender equality in order to realize God's mission in the world. Women's lives have changed dramatically over the last quarter century. Progress on gender equality is still limited. The patriarchal culture that is still strong prolongs the suffering of the powerless and complicates the struggle and change towards justice and gender equality. Discrimination against women is a common problem in almost all occupations, even in most parts of the world. We can understand that gender is a difference that is not biological or not divine in nature. Through this article, the author wants to raise the theme of gender equality which is discussed based on the Catholic Church document, Gaudium Et Spes art. 29. This research uses a type of library research, which has the aim of tracing and analyzing data or information about the essence of the Gaudium Et Spes document Articles 9 and 29 in relation to Gender Equality. Gaudium Et Spes contribution document Articles 9 and Art. 29 is the similarity between men and women is through the institution of good will in the sense that both men and women participate in what the church stands for, namely the struggle to shape human life in a more humane way. The Catholic Church also emphasizes that this will take a long time, considering that the struggle for gender equality is not easy, especially in a world that is heavily influenced by patriarchalism social life.